Images from Scenes of the Day of Judgment - Hala Adnan Mohammed, (Islamic Sciences Journal, 2025)
The Day of Judgment means that God Almighty will stand before His servants and make them aware of the deeds they did in their worldly lives, whether they believed or disbelieved. It is called the Day of Judgment because it is the day of accountability, discussion and questioning. The first horror that will occur is the blowing of the Trumpet. The sky will burst and split, leading to its destruction and disappearance, and only the One, the Prevailing, will remain. All the people were displayed in rows, barefoot, naked, and uncircumcised. The books are placed in the hands of their owners, who do not leave anything small or large without counting it. As for he who is given his book in his right hand, and they are the people of Paradise, he will know that he is among the people of Paradise. He says: Here, read my book. That is when God gives permission. He reads his book and enters Paradise, and on their faces are signs of joy. As for the people of Hell, you will see them lowering their heads before their Lord out of shame and remorse; blaming one another. As for the people of Hell, Hell will be a torment, their clothing will be a torment, their bedding and their blankets will be a torment, so everything will be a torment upon them.